2014
DOI: 10.1093/rheumatology/keu162
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical prediction of osteoporosis in a contemporary cohort of patients with rheumatoid arthritis

Abstract: The prevalence of osteoporosis in RA remains high in the modern era despite aggressive management and the use of biologic therapy. Most RA patients with osteoporosis can be identified by a simple algorithm taking age and BMI into account.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 21 publications
5
71
4
4
Order By: Relevance
“…We note, however, that incidence rates of vertebral and hip fracture observed among patients unexposed or exposed to low levels of steroids in our study are comparable to those reported for post-menopausal women aged 50-70 years in the general population [31,32]. In contrast to previous studies of glucocorticoid users with diverse disease [15,[33][34][35][36][37], we may have better isolated the impact of glucocorticoid use on fracture risk by focusing on incident RA patients and, thus, decreasing the potential for disease-related confounding. This approach also reduced the heterogeneity in patterns of steroid use, which varies by disease.…”
Section: Discussioncontrasting
confidence: 55%
“…We note, however, that incidence rates of vertebral and hip fracture observed among patients unexposed or exposed to low levels of steroids in our study are comparable to those reported for post-menopausal women aged 50-70 years in the general population [31,32]. In contrast to previous studies of glucocorticoid users with diverse disease [15,[33][34][35][36][37], we may have better isolated the impact of glucocorticoid use on fracture risk by focusing on incident RA patients and, thus, decreasing the potential for disease-related confounding. This approach also reduced the heterogeneity in patterns of steroid use, which varies by disease.…”
Section: Discussioncontrasting
confidence: 55%
“…This agrees with hAuser et al, 2014 who evaluate the clinical predictors of osteoporosis in RA in a cohort and found that women had significantly lower BMD [46].…”
Section: Discussionsupporting
confidence: 90%
“…Excess bone loss seen in RA occurs early in the disease 75 . Recent studies from the era of biologics (and low prevalence of post-menopausal HRT) continue to show excess osteoporosis in RA patients compared to age-matched controls (30% versus 17.4%), and an association with menopause 76 . HRT reduces bone resorption regardless of glucocorticoid therapy in post-menopausal RA patients 77,78 , but there are, of course, other potential health concerns with post-menopausal HRT.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%